Characterization of monoclonal antibodies generated to the 287–302 amino acid loop of the human epidermal growth factor receptor. (29th November 2019) - Ho, Eric Chun Hei; Antignani, Antonella; Sarnovsky, Robert; FitzGerald, David
Abstract: Background: The dysregulation of epidermal growth factor receptor (EGFR) has been implicated in the oncogenesis of various malignancies including glioblastoma and some epithelial cancers. Oncogenesis occurs from the overexpression of EGFR, often linked to gene amplification or receptor mutagenesis. The 287–302 loop in the extracellular domain is exposed completely on EGFR variant III (EGFRvIII), partially exposed on some cancers but cryptic on normal cells. We report on the generation of antibodies to this loop. Methods: The 286–303 peptide was coupled chemically to keyhole limpet hemocyanin. After immunizations, sera were assayed for reactivity to the peptide. Mice with high titers were used for hybridoma production. Purified antibodies were isolated from hybridoma supernatants, while V regions were cloned and sequenced. Receptor binding was characterized using enzyme-linked immunosorbent assay and flow cytometry. A recombinant immunotoxin was generated from the 40H3 antibody and its cytotoxic activity characterized on relevant cancer cell lines. Results: Seven monoclonal antibodies were generated to the 287–302 loop and characterized further. Each one reacted with EGFRvIII but not wild-type EGFR. Based on reactivity with the immunizing peptide, antibodies were mapped to one of three subgroups. One antibody, 40H3, also exhibited binding to MDA-MB-468 and A431 cells but not to non-cancerous WI-38 cells. Because of its unusual binding characteristics, a recombinant immunotoxin was generated from 40H3, which proved to be cytotoxic to MDA-MB-468, A431 and F98npEGFRvIII expressing cells. Conclusions: Immunization with a peptide corresponding to a cryptic epitope from EGFR can produce tumor cell-binding antibodies. The 40H3 antibody was engineered as a cytotoxic recombinant immunotoxin and could be further developed as a therapeutic agent.